2014
DOI: 10.1038/sc.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair appropriateness in patients with spinal cord injury: a Turkish experience

Abstract: Study design: Descriptive. Objective: To determine the wheelchair appropriateness in patients with spinal cord injury (SCI). Setting: National Rehabilitation Center in Ankara, Turkey. Methods: Twenty-seven (25 male, 2 female) SCI patients were included. Demographic and clinical characteristics of the patients were noted. All wheelchairs were evaluated considering each part (seat length, seat depth, seat height, back height, armrest, headrest, wheels and seat belt) by a physiatrist who had attended the wheelcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Appropriate wheelchairs, which are a prerequisite for mobility and function, are hard to obtain and afford in most lower income countries [34], even worse in the rural settings. In Tanzania particularly the setting for this study, more days are spent in the hospital by persons with TSCI awaiting a donated or subsidized wheelchair, as they cannot afford one by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate wheelchairs, which are a prerequisite for mobility and function, are hard to obtain and afford in most lower income countries [34], even worse in the rural settings. In Tanzania particularly the setting for this study, more days are spent in the hospital by persons with TSCI awaiting a donated or subsidized wheelchair, as they cannot afford one by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, 55-68% of wheelchair users use inappropriate wheelchairs (e.g. inappropriate seat height, cushion and back height) due to factors such as users' obtaining wheelchairs without a prescription, wheelchairs were prescribed by non-specialized centres, errors in prescription and construction of wheelchairs, and challenges with insurances and refunding systems [48,49]. In order to reduce/prevent fall risk and fall-related injuries, improvements in accessibility of wheelchair prescription and appropriate follow-up are needed for wheelchair users living in the community [48,49].…”
Section: Plos Onementioning
confidence: 99%
“…In general, only a few clinical studies have been conducted to evaluate the effectiveness of commercially available static and dynamic head supports with wheelchair users [5,[21][22][23]. Moreover, case studies and case series were found reporting the outcomes after implementation of (customised) head support solutions or wheelchair systems [24][25][26][27], as well as cross-sectional surveys for several user groups [28][29][30]. Other non-clinical studies describe the development [31][32][33][34] and system testing [35][36][37] of wheelchair mounted head support systems.…”
Section: Scoping Review Resultsmentioning
confidence: 99%